Ambiguitas Konstitusional dalam Fungsi Legislasi Presiden dan DPR di Indonesia - Nefaldy, Muhammad Farhan; Situmeang, Tomson (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2026)
The Indonesian system of government has evolved significantly through constitutional amendments which aimed at strengthening the presidential system. However, overlapping authority between the President and the House of Representatives (DPR) in the lawmaking process continues to generate constitutional ambiguity, particularly regarding the separation of powers. This study examines the balance of legislative authority between the President and the House of Representatives under the 1945 Constitution using a normative juridical method with a historical approach, analyzed through Montesquieu’s theory of the separation of powers. The analysis reveals that Article 5 paragraph (1) and Article 20 paragraphs (1) and (2) contribute to overlapping legislative functions between the two institutions. To address this issue, the study proposes limiting the President’s legislative initiative, strengthening checks and balances through the DPR and public participation, and reinforcing the role of the Constitutional Court as a constitutional guardian. These measures are expected to enhance constitutional clarity and strengthen Indonesia’s presidential system in accordance with democratic principles.